Combined effect of surface microgeometry and adhesion in normal and sliding contacts of elastic bodies - Irina Goryacheva; Yulia Makhovskaya (Friction)
Abstract In this study, models are proposed to analyze the combined effect of surface microgeometry and adhesion on the load–distance dependence and energy dissipation in an approach–separation cycle, as well as on the formation and rupture of adhesive bridges during friction. The models are based on the Maugis–Dugdale approximation in normal and frictional (sliding and rolling) contacts of elastic bodies with regular surface relief. For the normal adhesive contact of surfaces with regular relief, an analytical solution, which takes into account the mutual effect of asperities, is presented. The contribution of adhesive hysteresis into the sliding and rolling friction forces is calculated for various values of nominal pressure, parameters of microgeometry, and adhesion.